The estimation of semen production based on body weight and scrotal circumference on PO Bull at Singosari National Artificial Insemination Center - Muthiapriani, L.; Herwijanti, E.; Novianti, I.; Furqon, A.; Septian, W. A.; Suyadi, Suyadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
Ongole Crossbred cattle or more popular known as Peranakan Ongole (PO) cattle is one of local breeds cattle in Indonesia. For improving the population and genetic quality, superior bull with high capacity to produce semen is seriously required. This study aimed to find out the estimation value of semen production of PO bull based on body weight and scrotal circumference. A total sampling of 9 bull candidates of PO cattle available at National Artificial Center (NAIC) Singosari, Malang, Indonesia were used in this study. The method used was case study. Scrotal circumference was directly measured as a primary data. While body weight, semen volume, semen concentration and sperm motility were collected from BBIB Singosari from secondary data. Data was analyzed using simple linear regression. The results showed that with the limited number of samples, there is no significant correlation (P>0.05) between body weight and scrotal circumference on semen volume, semen concentration, and sperm motility.  It was concluded that with limited number of samples involved in this study, there was no significantly on semen production based on body weight and scrotal circumference on PO bull. The suggestion was to improve the correlation value and significant result. The number of samples should be increased.